Comparative European politics (Houndmills, Basingstoke, Hampshire, England : Palgrave Macmillan, 2003)
Focuses on the comparative politics and political economy of contemporary Europe within and beyond the European Union, the processes of European integration and enlargement, and the place of Europe and European states within international/global political and economic dynamics.
Title from volume contents page (viewed Nov. 11, 2003).
Vol. 16, no. 4 (July 2018) (Springer Link, viewed July 20, 2018).
Keywords: European Union -- Periodicals; European Union; Since 1989; Economic policy; International economic integration; Diplomatic relations; Politics and government; Europe -- Politics and government -- 1989- -- Periodicals; Europe -- Economic policy -- Periodicals; Europe -- Economic integration -- Periodicals; Europe -- Foreign relations -- 1989- -- Periodicals; Europe -- Politique et gouvernement -- 1989- -- Périodiques.; Europe -- Politique économique -- Périodiques.; Europe -- Intégration économique -- Périodiques.; Europe -- Relations extérieures -- 1989- -- Périodiques.; Pays de l'Union européenne -- Périodiques.; Europe; Electronic journals